Problematic Gaming and Internet Use but Not Gambling May Be Overrepresented in Sexual Minorities – A Pilot Population Web Survey Study - Broman, Niroshani; Hakansson, Anders (Frontiers in Psychology, 2018)
Background: Substance-related addictive disorders are known to be overrepresented in non-heterosexual individuals, but it is largely unknown whether this is also the case for behavioral addictions such as problem gaming and gambling. This study aimed, in a pilot web survey design, to assess whether problematic gambling, gaming and internet use may be more common in individuals with a non-heterosexual orientation. Methods: An online survey was distributed through media and social media, and answered by 605 individuals (51% women and 11% non-heterosexual). Problem gambling, problem gaming and problematic internet use were measured through structured screening instruments (the CLiP, the GAS and the PRIUSS, respectively). Results: Problem gaming and problematic internet use were significantly more prevalent in non-heterosexual subjects. Instead, problem gambling did not differ between heterosexual and non-heterosexual respondents. Psychological distress and social media use for more than 3 h daily were significantly more common in non-heterosexual respondents. In the overall sample, gaming and gambling were associated statistically. Conclusion: Based on the present pilot online survey, problematic gaming and internet use, but not problem gambling, may be more common in non-heterosexual populations. This area merits more and larger studies, and potentially preventive efforts aimed for non-heterosexual individuals in the population. Possible explanations and study limitations are discussed in the paper.